HRTEM and EELS investigations of flame-formed soot nanostructure. (1st August 2018) - Apicella, B.; Ciajolo, A.; Tregrossi, A.; Abrahamson, J.; Vander Wal, R.L.; Russo, C.
Highlights: Soot nanostructural characterization in a methane flame starting from its inception. Coupling of nanostructural and chemical techniques for soot characterization. A structural improvement was observed with aging along the flame. Most of the nanostructural restructuring appears associated to the inception phase. Abstract: High resolution transmission electron microscopy (HRTEM) and electron energy loss spectroscopy (EELS) were applied to soot probed along a premixed methane flame from the inception phase up to the burnout region in order to follow the transformations of soot nanostructures. The nascent methane soot presented the predominance of large coalesced disordered structures in comparison to young, intermediate and mature soot presenting spherule aggregates. Quantitative structural information describing the shape, size and orientation of sp 2 -bonded (aromatic) layers and their distribution inside the carbon particle were obtained by HRTEM image analysis. A moderate structural improvement in terms of a better stacking of longer and more planar layers along with the tortuosity fringe decrease was observed along the methane flame. EELS was instead used to provide quantitative information about the relative concentrations of sp 3 and sp 2 hybridized carbon. It is the first time that quantitative EELS is applied to soot from the inception to maturation along a premixed laminar flame. The aromatic content for the nascent soot resulted to be rather high (84%) indicating the predominant aromatic character of soot precursors. The steep increase of sp 2 content from 84 to 94% in the passage from nascent to young soot was noteworthy. The similar sp 2 content (94–96%) as well as the invariance of fringe length of young, intermediate and mature soot testified that most of the structural changes occurred at the inception, after then methane soot did not undergo a significant nanostructural restructuring, possibly because of the less reactive environment generated from methane combustion.